Evaluation of different foliar fertilizers on the crop production of sugarcane - Raposo Jr., Jorge Luiz [UNESP]; Gomes Neto, José Anchieta [UNESP]; Sacramento, Luis Vitor Silva [UNESP] (Taylor & Francis, 2013)
Influence of different foliar fertilizers (phosphite, micronutrients, biostimulant, phosphite + micronutrients, phosphite + biostimulant, micronutrients + biostimulant and phosphite + micronutrients + biostimulant) on yield of sugarcane was evaluated after fertilization at 30, 90 and 150 days after harvesting two-year-old sugarcane. The experiment was carried out in a commercial crop employing a randomized block design in four replicates. Higher stalk masses were observed for fertilization at 30 days after harvest, and the higher content of sucrose, total recoverable sugar and Brix degrees were observed for sugarcane fertilized after 150 days. Statistical analysis (Duncan's test) revealed no significant variation (P & 0.05) in Brix degree, sucrose content and total recoverable sugar. For total recoverable sugar x stalk weight (the main payment type for sugarcane producers), the following sequence (time treatment, fertilizer composition) 30-days, micronutrient + biostimulant; 150-days, biostimulant; and 90-days, biostimulant increased 11%, 17%, and 21% the yield of sugarcane. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: cane yield; foliar fertilizers; plant nutrition; Saccharum